HUBUNGAN INTENSITAS PENGGUNAAN MEDIA SOSIAL DENGAN KECENDERUNGAN SOCIAL COMPARISON DAN PERILAKU INSECURE PADA REMAJA - Lastri Nita Shela; M. Fahli Zatrahadi; Miftahuddin (STKIP Subang, 2026)
The development of social media in the digital era has a significant impact on the lives of adolescents, particularly in the formation of self-concept and psychological conditions. High intensity of social media use causes adolescents to be more frequently exposed to various content that depicts ideal lives, beauty standards, and the achievements of others, thus encouraging the emergence of social comparison tendencies and insecure behavior. This study aims to determine the relationship between the intensity of social media use and the tendency of social comparison and insecure behavior in adolescents. The method used in this study is library research using secondary data in the form of national journals, books, and scientific articles from the last five years relevant to the research topic. Data collection techniques were carried out through documentation and literature searches from Google Scholar and accredited national journal portals, then analyzed using qualitative descriptive analysis. The results of the study indicate that the intensity of social media use has a significant relationship with the increasing tendency of social comparison and insecure behavior in adolescents. The higher the social media use, the greater the tendency of adolescents to compare themselves with others, resulting in feelings of inferiority, lack of self-confidence, social anxiety, and dissatisfaction with themselves. Therefore, self-control, digital literacy, and family and environmental support are needed so that adolescents can use social media healthily and wisely.